Analisis Keterampilan Proses Sains (KPS) Dalam Buku Teks IPA SMP Kelas VII Tema Pemanasan Global: (Analysis Of Science Process Skills (SPS) In Science Textbook Grade7th Junior High School On The Theme Global Warming) - Nahlin Mutia Solpa; Lukman Nulhakim; Vica Dian Aprelia Resti (BIODIK, 2022)
The purpose of this study is to describe the availability of the Science Process Skills (SPS) component in a seventh grade science textbook for junior high school students with a global warming topic. The aspects of SPS analyzed are observing, classifying, interpreting, asking questions, using tools and materials, applying concepts and communicating.  This is a descriptive study that makes use of the documentation analysis method  to describe the emergence of SPS indicators for each sub-material which is summarized in the theme of global warming in science textbooks.  The objects of this research are science textbooks published by the Ministry of Education and Culture and science textbooks published by Erlangga.  In this study, documentation approaches were used to obtain data.  The instrument used in this study was asheet instrument checklist.  Descriptive statistics are used to analyze research data by computing the number of components of the analysis according to the SPS aspect. The findings of the study of the formation of the SPS component in science textbooks, the emergence of the SPS aspect that dominates is in Book 1 of the Kemendikbud publisher with a percentage level of 75% in the Appropriate category.  Meanwhile, Book 2 was published by Erlangga, with a percentage rate of 54% appearing in the SPS aspect with a fairly appropriate category.  Based on this, Book 1 publisher of the Ministry of Education and Culture is more supportive in developing students' Science Process Skills (SPS). Keywords: Science Process Skills (SPS), Class VII Junior High School Science Textbook, Global Warming   ABSTRAK Tujuan dari penelitian ini adalah menjelaskan gambaran ketersediaan aspek Keterampilan Proses Sains (KPS) dalam buku teks pelajaran IPA SMP kelas VII tema pemanasan global.  Aspek KPS yang dianalisis adalah aspek mengamati, mengelompokkan, menafsirkan, mengajukan pertanyaan, menggunakan alat dan bahan, menerapkan konsep dan berkomunikasi.  Penelitian ini merupakan penelitian deskriptif dengan pendekatan analisis dokumentasi untuk menggambarkan kemunculan indikator KPS setiap sub materi yang terangkum dalam tema pemanasan global dalam buku teks IPA.  Objek penelitian ini adalah buku teks IPA terbitan Kemendikbud dan buku teks IPA terbitan Erlangga.  Dalam penelitian ini, pendekatan dokumentasi digunakan untuk memperoleh data. Instrumen yang digunakan dalam penelitian ini adalah instrumen lembar checklist. Analisis data penelitian menggunakan statistik deskriptif dengan menghitung jumlah komponen analisis sesuai dengan aspek KPS.  Hasil analisis kemunculan aspek KPS pada buku teks IPA yang dianalisis, kemunculan aspek KPS yang mendominasi yaitu pada Buku 1 penerbit Kemendikbud dengan tingkat persentase sebesar 75% dengan kategori Sesuai.  Sedangkan Buku 2 penerbit Erlangga dengan tingkat persentase kemunculan aspek KPS sebesar 54% dengan kategori cukup sesuai.  Berdasarkan hal tersebut, Buku 1 penerbit Kemendikbud lebih menunjang dalam mengembangkan Keterampilan Proses Sains (KPS) siswa. Kata kunci: Keterampilan Proses Sains, Buku teks IPA SMP kelas VII, Pemanasan Global